2018
DOI: 10.1007/s11199-018-0934-4
|View full text |Cite
|
Sign up to set email alerts
|

Video Game Playing and Beliefs about Masculinity Among Male and Female Emerging Adults

Abstract: Video games have been soundly critiqued for their depiction of gender and emerging research has shown than playing can be associated with holding stereotypical or narrow views of gender roles and norms. Yet, rarely has past research focused particularly on correlations between video game playing and perceptions of masculinity, in particular, despite critique of gaming content and culture as a space where a type of hypermasculinity thrives. The current study explores the role of overall amount of time spent wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 67 publications
2
32
1
7
Order By: Relevance
“…Also, previous research has suggested that stereotype threat can be represented by participants reporting the opposite behavior to the stereotype to disconfirm it (Pennington et al, 2016), which did not seem to be evident in this current research, but we acknowledge that stereotype threat could still be influencing participants responses. Especially, as previous research found that violent video games could be facilitating ideas and beliefs around traditional masculinity from both male and female participants (Blackburn and Scharrer, 2019). Although it should be noted that a high majority of the participants both male and female were playing video games which was similar to the Entertainment Software Association statistics (ESA, 2019) and demonstrates that gaming is an activity which both males and females engage with.…”
Section: Discussionsupporting
confidence: 60%
“…Also, previous research has suggested that stereotype threat can be represented by participants reporting the opposite behavior to the stereotype to disconfirm it (Pennington et al, 2016), which did not seem to be evident in this current research, but we acknowledge that stereotype threat could still be influencing participants responses. Especially, as previous research found that violent video games could be facilitating ideas and beliefs around traditional masculinity from both male and female participants (Blackburn and Scharrer, 2019). Although it should be noted that a high majority of the participants both male and female were playing video games which was similar to the Entertainment Software Association statistics (ESA, 2019) and demonstrates that gaming is an activity which both males and females engage with.…”
Section: Discussionsupporting
confidence: 60%
“…Therefore, the gendered nature of esports conversation is not surprising, but it is worth asking to what extent it exists in regular gameplay rather than in virtual chatrooms. Much of the video game universe strictly adheres to and reinforces gender stereotypes while the myth of gaming as incongruent with feminine identity persists (Blackburn & Scharrer, 2019;Kim, 2017;Paaßen et al, 2017) This lack of inclusivity among esports environments largely differs from that of traditional sport. Due to the fact that many competitive settings for esports players are based within online environments with a shield of anonymity, discrimination and hostility toward females is likely to ensue (Ruvalcaba et al, 2018;Kim, 2017).…”
Section: Hostility In Esportsmentioning
confidence: 99%
“…Similarly, more research is needed to support the links among exposure to sexually objectifying media, empathy toward women, and sexual harassment proclivity. Moreover, strong evidence indicates that exposure to sexually objectifying media enhances consumers' endorsement of traditional masculine and feminine norms (Blackburn and Scharrer 2019;Wright and Tokunaga 2015) and that endorsement of gender norms reduces empathy with victims of violence (Gabbiadini et al 2016). However, research testing the path from shift in gender norms to bystander intervention is still absent.…”
Section: Weak Connectionsmentioning
confidence: 99%